Uji Karateristik Briket Serbuk Kayu Terhadap Laju Pembakaran - Siregar, Zufri Hasrudy; Mawardi, Mawardi; Alhadi, Rafli; Sembiring, Anita Christine (universitas teuku umar, 2023)
The burning rate is used to measure the quality of sawdust briquettes. In this study, sawdust briquettes were selected as the primary raw material and studied how the properties of briquettes affect the rate of combustion. Sawdust briquettes are considered a potential alternative to address problems that arise with using conventional fuels. Sawdust briquettes are made during the research process using various compositions and manufacturing techniques. Combustion tests are also performed on briquettes in the laboratory by tracking the combustion rate. The results showed that the process of authoring and carbonization of new teak sawdust resulted in charcoal yields of 37.30% and 40.70% for lam teak, respectively. The results of laboratory testing on manufacturing charcoal briquettes with which the igniter material is added are overall excellent. Several parameters, such as the calorific value (7970.668 cal/gram and 8291.831 cal/gram), the volatility of substances (9.957%), and the yield of charcoal is 37.30%.